Analysis of microrna derived from saliva- and plasma-exosome as potential biomarker(s) for chronic periodontitis - Kamal, Nik Nur Syazana Nik Mohamed (2021)
Chronic periodontitis (CP) is an oral cavity disease arising from chronic inflammation of the periodontal tissues. Exosomes are lipid vesicles enriched in specific microRNAs (miRNAs), potentially providing a disease-specific diagnostic signature. miRNAs have been demonstrated to play an important role in regulating the immuno-inflammatory response; however, the function of salivary and plasma exosomes miRNAs in chronic periodontal inflammation has not been investigated. To assess the value of exosomal miRNAs as potential biomarkers for CP, miRNA expression were profiled using Agilent miRNA microarray platform. From 2,549 tested miRNAs, 1,985 were significantly down-regulated and 10 significantly upregulated in CP saliva samples; whereas 33 miRNAs were significantly downregulated in CP plasma samples; as compared to respective healthy samples. Expression of hsa-miR-5006-5p, hsa-miR-942-3p, hsa-miR-30e-3p and hsa-miR- 199a-3p was validated using reverse transcription quantitative polymerase chain reaction (RT-qPCR) method. RT-qPCR results recorded significant replicable miRNAs profiling results, strengthening the potential of these miRNAs to be developed into biomarker(s) for the disease. For in vitro study, human gingival fibroblasts (HGFs) cells were induced with lipopolysaccharides (LPS) from Porphyromonas gingivalis to mimic inflammation condition, whereas the miRNA mimics were used for transfection. hsa-miR-30e-3p mimic was transfected either before or after induction of LPS to test the reaction of the mimic towardsinflammation condition. hsa-miR-30-3p level was only significantly up-regulated after the induction, resembling the ability of the mimic to act as healer rather than as a shield. Lastly, the hsa-miR-5006-5p and hsa-miR-30e-3p mimics were transfected into HGFs cells and expression of bone morphogenetic protein receptor type II (BMPR2), interleukin 1 receptor 1 (IL1R1), nuclear factor kappa B subunit 1 (NFκB1) and TLR4 were quantified. The BMPR2, IL1R1, NFκB1 and TLR4 were found significantly down-regulated in both types of transfected cells (either transfected with hsa-miR-5006-5p-mimic or hsa-miR-30e-3p-mimic). Yet, only the significant down-regulation of BMPR2 in transfected cells-with hsa-miR-5006-5pmimic parallel with extrinsic inflammation effect, making BMPR2 as the direct target gene for hsa-miR-5006-5p. Meanwhile, the significant down-regulation of IL1R1, NFκB1 and TLR4 in transfected cells-with hsa-miR-30e-3p-mimic parallel with opposite extrinsic inflammation effects, making them as the potential direct target genes for hsa-miR-30e-3p. Although extensive mechanism study is necessary in future, nevertheless, the replicable results from miRNAs profiling, RT-qPCR, and in vitro study (especially for transfection of hsa-miR-30e-3p/ LPS induction experiments), are nough to ensure the high potential of these miRNAs as biomarkers for CP.